ANALISIS KOMPARATIF PENDAPATAN USAHATANI KAKAO SAMBUNG SAMPING DAN SAMBUNG PUCUK DI DESA SIDOLE BARAT KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - fahruddin, Hamdan; Kalaba, Yulianti; Sulaeman, Sulaeman (AGROTEKBIS, 2019)
This research aims to find out income comparison between cocoa farming of side grafting and top grafting. This research was conducted at West Sidole village of Ampibabo Sub-District, District of Parigi Moutong with the respondents was 30 respondents from 2 population were of 125. Cacao farmers were consisted of 17 cocoa farmers used side grafting and 13 cocoa farmers used top grafting (Propotional Stratified Random Sampling). The approach was taken to answer this goal is income analysis, it is rasio between revenue and total cost. The research result showed that the average cocoa farming income of side gfarting was Rp.42.304.095,12/ha/year, while cocoa farming income of top grafting was Rp.22.563.561,09/ha/year. It can be concluded that cocoa farming income of side grafting is bigger than cocoa farming of top grafting.